An investigation on cervical cancer and human papillomavirus vaccine knowledge, and analysis of influencing factors for choosing domestic or imported 2vHPV vaccine among females in Shenzhen, China - Linxiang Chen; Fangfang Lu; Ziqi Wang; Hanqing Chen; Mianling Chen; Chunmiao Peng; Kangming Chen; Cuili Chen; Huawei Xiong; Xu Xie (Taylor & Francis Group, 2023)
In 2020, the domestic (Chinese native) 2v human papillomavirus (HPV) vaccine was approved for use in females. At present, there are obvious differences in demand for different HPV vaccines. We aimed to investigate knowledge level of cervical cancer and HPV vaccine and its influencing factors among the eligible female recipients in Shenzhen, China, and to analyze the factors influencing choice of 2vHPV vaccine (domestic or imported) would be selected. A self-administered questionnaire was carried out on this investigation, and respondents were selected by random sampling method conducted by vaccination doctors. A total of 1197 valid questionnaires were collected, of which 729 (60.9%) were vaccinated with domestic vaccines and 468 (39.1%) were vaccinated with imported. Four hundred and fifty (61.7%) and 306 (65.4%) got a passing grade, respectively (χ2 = 1.637, P = .201). Logistic regression analysis showed that age (P = .002), ethnicity (P < .001), duration of residence in Shenzhen (P < .001), educational level (P < .001) and occupation (P < .001) were significant. It also showed that the manufacturers (P < .001), efficacy (P < .001), safety (P < .001), cognitive approach (P < .001), public opinion (P < .001), convenient acquisition (P < .001) and knowledge reserve (P = .035) were statistically significant. While price (P = .371) and doctor's suggestion (P = .114) were not. In conclusion, eligible female recipients had a high degree of knowledge regarding cervical cancer and HPV vaccine, education level and occupation were the most important factors for scores. Domestic 2vHPV vaccine was more widely utilized than imported, manufacturer, efficacy, safety, cognitive approach, public opinion, convenient acquisition, and knowledge reserve had an impact on selection for recipients, while price and doctor's suggestion did not.